The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5751/es-04836-170216
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Work: Engaging Knowledge Systems in Co-management of Feral Animals on Indigenous Lands

Abstract: ABSTRACT. The integration and use of Indigenous knowledge to inform contemporary environmental policy decisions and management solutions is a growing global phenomenon. However, there is little critical inquiry about how the interactions between scientific and Indigenous knowledge (IK) systems can be effectively negotiated for the joint management of socialecological systems. Such issues are urgent on Indigenous lands where co-management efforts respond to pressing conservation agendas and where the contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 39 publications
(75 reference statements)
1
74
0
1
Order By: Relevance
“…Nevertheless, IPA planning processes are themselves invariably partnership processes because they involve collaboration and communication between traditional owners, planning facilitators, staff of the IPA Program, and often, bridging organizations. Robinson and Wallington's (2012) analysis of boundary work in the management of feral animals in a comanaged national park is indicative of the complexities that IPA planning facilitators face in translating meanings and brokering understandings. IPA plans, or the maps, diagrams, and vision statements included in them, might serve as boundary objects, that is, tools that are coproduced among various parties and that each party finds to be meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, IPA planning processes are themselves invariably partnership processes because they involve collaboration and communication between traditional owners, planning facilitators, staff of the IPA Program, and often, bridging organizations. Robinson and Wallington's (2012) analysis of boundary work in the management of feral animals in a comanaged national park is indicative of the complexities that IPA planning facilitators face in translating meanings and brokering understandings. IPA plans, or the maps, diagrams, and vision statements included in them, might serve as boundary objects, that is, tools that are coproduced among various parties and that each party finds to be meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…Huntington urges Western scientists to carefully consider how they use the term traditional knowledge, to define it clearly and carefully to avoid misrepresenting the knowledge, and to recognize that there may be distinctions in types of knowledge within the community. Robinson and Wallington [67] raise a similar point and note the importance of establishing a relationship with the community that will facilitate the outsiders' understanding and use of traditional knowledge. Latiluppe claims that for "TK to advance the priorities and goals of Indigenous research partners and to be of benefit to Indigenous peoples, it is paramount that researchers consider their positionality and anticipate the outcomes of particular approaches within situated contexts" [74].…”
Section: Braiding Traditional Knowledge With Water Managementmentioning
confidence: 99%
“…Robinson and Wallington examined the integration of indigenous knowledge into co-management systems in Australia and found that managers needed to take into account the institutional landscapes as well as current socio-ecological landscapes, because older management or legal structures can inhibit the development of new co-management structures. Boundaries can also create barriers to collaboration [67]. Robinson and Wallington [67] identified three factors in effective boundary work: meaningful participation in setting goals and co-producing knowledge; governance to ensure that boundary work is accountable; and co-production of boundary objects (e.g., maps, or interpretive frameworks that all participants agree to as trustworthy and respectful of their differences).…”
Section: Collaborative Approaches To Natural Resource Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…First, some challenges relate to the limitations of collaborative governance in the face of deep-seated conflict, culture or power barriers (Hill et al, 2012;Leach and Pelkey, 2001). For example, several researchers note the difficulty of applying collaborative management in developing countries with authoritarian governments and deep-seated regional animosities (Dore, 2007;Wegerich, 2007) or in cross-cultural contexts where democratic approaches to stakeholder engagement and building consensus is not appropriate (Robinson and Wallington, 2012). It is also important to note that these are also limitations of traditional governance approaches.…”
Section: Challengesmentioning
confidence: 99%